Kurikulum Merdeka dan Humanisme Pendidikan: Rekonstruksi Filosofis Pembelajaran Berpusat pada Peserta Didik - Frengki Lado; Marince Dila Fallo; Maria Indriani Sesfao (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The implementation of the Independent Curriculum in the Indonesian education system is a strategic step towards realizing relevant, meaningful learning that is oriented towards character building for students. This curriculum not only emphasizes academic achievement but also prioritizes holistic human development through an approach aligned with the principles of educational humanism. Educational humanism views students as learning subjects with potential, dignity, and uniqueness that must be respected in every educational process. Through student-centered learning, the Independent Curriculum presents differentiated, contextual, dialogical learning practices, as well as formative and authentic assessments that support the development of positive student character. The implementation of the Pancasila Student Profile Strengthening Project (P5) is a concrete manifestation of the integration of humanistic values ​​in learning, which encourages the growth of empathy, mutual cooperation, responsibility, tolerance, and social awareness. Furthermore, the philosophical reconstruction of student-centered learning shifts the educational paradigm from a mechanistic approach to a humanistic-constructivist approach that emphasizes meaningful learning experiences and self-actualization. The role of teachers has transformed into facilitators and learning companions who build dialogic relationships and inclusive learning environments. Thus, the Independent Curriculum, based on educational humanism, contributes significantly to shaping students' character, making them independent, possessing integrity, adaptable, and ready to face the challenges of 21st-century education.